PTU-019 REDUCe study: qualitative outcomes from a multi-centre mixed-methods feasibility RCT in cirrhosis-related palliative refractory ascites. (June 2019) - Cooper, Max; Pandey, Aparajita; Pollard, Alex; Macken, Lucia; Evans, Catherine; Steer, Shani; Hashim, Ahmed; Verma, Sumita; Mason, Louise
Abstract : Introduction: The REDUCe study is a mixed methods feasibility randomised controlled trial (RCT) comparing palliative long term abdominal drains (LTAD) with standard care, recurrent large volume paracentesis (LVP) in advanced cirrhosis and refractory ascites (RA), where ineligible for liver transplantation (LT). Qualitative findings are reported here. Methods: Multicentre feasibility RCT with 1:1 randomisation between LTAD vs. LVP with 12 weeks follow up. This was a concurrent embedded qualitative study using telephone interviews with patients and health care professionals (HCP). All patient participants were offered an interview conducted post randomisation at a time preferred by them. The interviews explored experiences of participation (LTAD/LVP), benefit/risks and end of life care (EoLC). Thematic data analysis was supported by NVIvo software. Results: A total of 14 patient (LTAD n=6, LVP n=8) and eight HCP (five community and three hospital nurses) interviews were conducted. An additional five participants died rapidly. Interview uptake by patient participants was 88%. Two (14%), seven (50%) and five (36%) of the patient interviews occurred in the first, second and third month respectively after randomisation. LTAD appeared to transform multiple aspects of the patient pathway. Perceived benefits revolved around mitigating practical challenges associated with navigating hospital services, avoiding the tedium of lengthy waits inside the hospital and the inconvenience of spending whole days out of the house. Those in the LVP group expressed they would have preferred the LTAD. LTAD participants reported acceptability of the drain insertion process and aftercare. LTAD appeared to promote independence and mobility. However, one participant and two nurses reported temporary leakage problems which caused embarrassment and distress. Interviews suggested that continuity of care across the community and hospital was key. Regular home visits/telephone consultations provided valuable emotional support to patients/carers. Although the study participants had a limited life expectancy, nurse interviewees reported that some appeared not to have fully assimilated this information, and sometimes understood the LTAD as part of on-going active treatment rather than palliative care. Conclusions: Participants and nurses expressed acceptability of palliative LTAD, and preference for this approach in enabling receipt of care at home. Study design enabled participation for patients with advanced cirrhosis. Some individuals however remained unaware of their limited life expectancy and palliative management. LTAD merit further assessment in advanced cirrhosis.